Carbon fluxes in the mixed layer of the Mediterranean Sea in the 1980s and the 2000s - Taillandier, V.; D'Ortenzio, F.; Antoine, David (Pergamon, 2012)
Mixed-layer CO 2 fluxes in the 1980s (1979–1983) and the 2000s (1998–2001) are assessed in the Mediterranean Sea. The analysis uses an array of one-dimensional physical–biological–chemical coupled models covering all areas where depth is greater than 300m. These models are driven by surface heat fluxes and wind stress, and surface chlorophyll concentrations. This approach provides estimations of basin-scale oceanic CO 2 levels over two time periods separated by a 14-year gap and allows characterizing differences between these two periods. The results indicate that the Mediterranean Sea was more biologically productive (by about 16gCm -2 y -1 ) during the 2000s, with an increase of carbon export to deep layers by about 7gCm -2 y -1 as compared to the 1980s. The consecutive modification of CO 2 fluxes toward deep layers did not, however, strongly modify the oceanic CO 2 levels, which differ by only ~5–10µatm between the two periods. The reason is the increase of atmospheric CO 2 levels by 30µatm between the two periods, which led to an increase of the CO 2 flux from the atmosphere to the ocean. The Mediterranean Sea was a CO 2 source to the atmosphere in the 1980s (about 1.5×10 12 molCy -1 ). It is close to equilibrium with the atmosphere in the 2000s (slight sink of about -0.2×10 12 molCy -1 ).